Analisis Biaya Modal Terhadap Tingkat Pengembalian Investasi Pada PT. Mitra Adiprakasa, Tbk. - Intan Fitriyani; Aris Munandar (Faculty of Economics and Business, Universitas Malikussaleh, 2020)
Capital costs are a major factor in the company's operational activities, including investment activities. The purpose of this study is to determine whether or not there is an effect of capital costs on investment returns at PT. Mitra Adiprakasa, Tbk. The method in this research is quantitative data. The population used is starting from 2004 since listing on (BEI) until 2018, with a research sample of 5 years. Samples were taken by purposive sampling with data collection methods in the form of literature study. The data analysis technique is a simple linear regression using IBM SPSS 20 software as a data tabulatoin tool. The data used are secondary data obtained from PT. Mitra Adiprakasa, Tbk. The results of this study indicate that there is no significant effect between the cost of capital and the rate of return on investment.